Metabolic syndrome, but not insulin resistance, is associated with an increased risk of renal function decline - Li, Youbao; Xie, Di; Qin, Xianhui; Tang, Genfu; Xing, Houxun; Li, Zhiping; Xu, Xiping; Xu, Xin; Hou, Fanfan (Clinical nutrition (Edinburgh, Scotland), 2015)
The purpose of this study was to evaluate the effect of metabolic syndrome (Mets) and insulin resistance (IR) on the risk of renal function decline (RFD) in a rural Chinese cohort. A total of 2696 subjects aged 40–71 years with normal renal function were followed-up for 7 years. RFD was defined using the Kidney Disease: Improving Global Outcome definition, i.e., a drop in estimated glomerular filtration rate (eGFR) category accompanied by a 25% or greater drop in eGFR from baseline or a sustained decline in eGFR of more than 5 mL/min/1.73 m2/year. During the 7-year follow-up, 9.0% of the subjects developed RFD. Subjects with Mets at baseline had an increased risk of RFD with an adjusted odds ratio (OR) of 1.77 (95%CI: 1.25–2.52), and there was a graded relationship between the numbers of Mets components and the risk for RFD. Exclusion of the subjects with hypertension (1.65; 0.99–2.75) or diabetes (1.86; 1.30–2.67) at baseline or further adjustment for IR (1.72; 1.15–2.57) did not substantially change the association between Mets and the risk of RFD. Moreover, the ORs of Mets status for RFD in the older group (≥55 years) were 2.14 (1.06–4.33) times of that in the younger group (<55 years) and 2.26 (1.07–4.78) times in hypercholesterolemia group (≥5.2 mmol/L) of that in the normal (<5.2 mmol/L) group. The baseline IR was not associated with the risk for RFD. Mets, but not IR, was associated with an increased risk for RFD. And there was a detrimental interaction of Mets with older age and hypercholesterolemia on the risk of RFD.